Jwanala Yuddha Karawitan Art Composition | Komposisi Seni Karawitan Jwanala Yuddha - I Made Purna Wijaya (GHURNITA: Jurnal Seni Karawitan, 2024)
Jwanala Yuddha is a work of Karawitan Art composition. This work was formed, motivated by the spirit of the mabuu-buu tradition in the Banjar Rangkakan area, Ketewel. This work uses Gamelan Selonding and several instruments from Gamelan Semara Pegulingan as a medium of expression. This Jwanala Yuddha work was created using the method of creating works of art by Alma M. Hawkins in her book entitled Creating Through Dance, which includes three stages, namely Exploration, Improvisation, and Forming. This work consists of three parts, each part has a character to implement the mebuu-buu tradition. There were 18 musicians involved in the creation of this work, including the author, and the duration of this work is around 11 minutes.